Educator Ethics: Abdul Fattah Abu Ghuddah's Perspective In The Book of Ar-Rosuul Al-Mu'allim Wa Asaalibuhu Fi At-Ta'liim - Lingga, Salman Al-Farisi; Ritonga, Sakti; Ritonga, Asnil Aidah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
This study examines the ethics of educators according to Sheikh Abdul Fattah Abu Ghuddah in the book